A novel combined model based on advanced optimization algorithm, and deep learning model for abnormal wind speed identification and reconstruction - Zhu, Anfeng; Zhao, Qiancheng; Shi, Zhaoyao; Yang, Tianlong; Zhou, Ling; Zeng, Bing (Energy (Oxford), 2024)
When the state of the sensors of the wind turbine, especially the anemometer, is abnormal, it will affect the correctness of other parameters of the whole power system. To recognize and reconstruct the abnormal data accurately and efficiently, this study proposes an improved complete ensemble empirical mode decomposition with adaptive noise (ICEEMDAN), extreme learning machine (ELM), crazy improve butterfly optimization algorithm (CIBOA), and bi-directional long short-term memory (BILSTM). In this system, the ICEEMDAN is utilized to decompose the original wind speed sequence, and then the ELM is employed as the initial prediction engine to extract the features of each sub-sequence to achieve the preliminary prediction outcomes. The CIBOA is employed to optimize the BILSTM model parameters. To further explore the unsteady features in the wind speed series, the residual results of the preliminary prediction are modeled using BILSTM, and the predicted residuals and preliminary results are integrated to obtain the final reconstructed values. In addition, the combined model is discussed in detail employing six assessment indicators, improvements of the reconstruction model, Diebold-Mariano test, operation time, and sensitivity analysis. The results indicate that the Pearson correlation coefficient (PCC) values of the proposed model are 0.9986, 0.9978, and 0.9979, respectively. It is concluded that the proposed hybrid reconstruction model accurately identifies and reconstructs abnormal wind speed, which provides a new technique for the reasonable utilization of wind energy. •Combines signal decomposition, multiple reconstruction modeling, intelligent optimization, and deep learning.•Initial and residual forecasts are applied simultaneously to identify and reconstruct abnormal wind speeds.•Improved intelligent optimization algorithm for parameter optimization.•Developed an abnormal wind speed identification and reconstruction system.